Papilomavírus humano : tratamento e acompamhamento de mulheres de um município do sul do Brasil - Ruggeri, João Batista (2015)
Cervical cancer (CC) still represents a major public health problem. The estimated incidence and of mortality rates in Brazil are gradually decreasing and presenting intermediate values in relation to developing countries. In 2014, the estimates in Brazil were of 15,590 new cases, with an average estimated risk of 15.33 cases per 100,000 women, with large variations in regional incidence rates. Several studies have described the incidence of HPV and its importance in the CC, but there is a scientific gap in relation to the follow-up and treatment of diagnosed cases in our region. The aim of this study was to investigate the risk behavior for CC prevalence and HPV resolution in women of a private network of a municipality in the Southern of Brazil. It is a descriptive and retrospective study with 25 women aged from 20 to 59 years of a private network healthcare attended by a specialized clinic in the period from January to December 2012 in a city in the Northwest of Parana State, Southern Brazil. Data medical records with cytological results and positive HPV were used. After treatment, these women were subjected to follow-up and after 6 months. Data were statistically analyzed using the t Test and Chi-square test with 5% significance. The samples were collected from the cervicovaginal region and were considered normal those exams who did not present: atypical squamous cells of undetermined significance (ASC-US) or does not exclude intraepithelial lesion high grade typical squamous cell high grade (ASC-H), atypical glandular cells (AGC), low grade (LSIL) or high grade (HSIL). Cervical squamous intraepithelial lesion of squamous cell cervical carcinoma in situ (ISCC) and invasive squamous cervical carcinoma (CC). The mean age of the women studied was of 27.76 ± 7.75 years, being the majority married, employed and non-smokers. The average age of menarche was of 13.00 ± 0.50 years and of 17.48 ± 1.78 years, was the first sexual intercourse, with only 8.0% (2) initiating sexual activity with about 15 years. Most of them had 1-2 children (60.0%) About 88.0% reported having a sexual partner throughout their lives, and all women were currently sexually active. About 68.0% used hormonal contraception methods. All women presented leukorrhea and pain and infection by a single HPV type. As for the degree of the lesion, 80.0% had high-risk and 20.0%, low-risk. The top-most prevalent risk HPV was of 16. The findings showed relevant information on the risk factors and HPV infection, in addition to the treatment and follow-up of 6 months in women economically and socially differentiated, with the absence of' traditional risk factors, corroborating with the information that different risk factors can be described in different populations. Thus, this study reinforces the fact that even women who do not have the usual risk factors should be subjected to follow-up and study of HPV in order to verify the prevalence of the infection, and indeed being subjected to a continuous monitoring to check persistent infection and promoting early diagnosis of the lesions, as well as appropriate treatment, preventing the occurrence of the CC.